IMPLEMENTACIÓN DE UN SISTEMA DE RECONOCIMIENTO DE HUELLA DIGITAL PARA OPTIMIZAR EL PROCESO DE CONTROL DE ASISTENCIAS EN LA EMPRESA SYSTEMATIC S.A.C., ICA-2019 - RICARDO FERNANDO, GALINDO ECHEGARAY (2020)
The purpose of this Project had as to implement a fingerprint recognition system to optimize the attendance monitoring process at the Systematic SAC company in the city of Ica. The attendance monitoring systems allow to manage for users attendance in a given área. Attendance monitoring have a lot of application in work environments, training centers, a mong others, as well as the computer system got to develop using Java as Programming Language and as SqlSever Database Management System 2014. The results were gotten by the efficiency test, indicates that the system is quite functional, safe and stable, since it satisfactorily programmer all the proposed activities, in the same way, it is an effective system since the response times in each operation are quite short. Keywords: fingerprint recognition system, Optimize, attendance monitoring